Lepisma saccharina - Prósperi, Germán Osvaldo (Universidad Nacional del Litoral, 2021)
The history of Western metaphysic is, according to an old theological tradition, a history of the Book. During the second half of 20th century, Jacques Derrida and Maurice Blanchot, among others, revisited this issue. The aim of this article is to demonstrate that: the operation Literature performs on the Book is analogous to the operation the insect lepisma saccharina performs on paper. I will use this analogy to illustrate that perversion or dislocation performed by Literature on the significant structure of the Book is even more extensive than in Derrida’s grammatology.